The title of the research: Indications of the structural formation of the hadith of the poet Jamil bin Muammar Al-Athari on the authority of Buthaina. - ابراهيم, نغم; عدنان محمد أحمد,; رباح علي, (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The study of the constructive formation of the poet Jamil bin Muammar al-Athri's speech about women reveals part of his vision that is artificially crystallized by the harmony and integration of his artistic units. Although the image of women in his poetry was manifested as a repetition of the images of women in the poems of the poets who preceded him, Jameel was able, through language, to transform it into an artistic equivalent of a wished world, a world he desired and felt a great need to belong to; The intense presence of the connotations of fertility, goodness, vitality, light, capacity, bliss and beauty and perfection and fullness, which he added to the woman, confirms that his talk about her was not praise or praise, or a description that tends to be sensual or virginal It was the creation of a visual world, ideal, desirable, extracted from the most beautiful images of reality. s structure.